Inventarisasi Spesies Ikan di Sendang Seruni Desa Tamansari, Kecamatan Licin, Kabupaten Banyuwangi - Mujib Rohman; Abdur Rohim Khuzain; David Pandapotan Batubara; Feonaldi Yanuar Prismatama (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Identifying fish species found in the Sendang Seruni stream, Tamansari Village, Licin District, Banyuwangi Regency, and analyzing the diversity and quality of its waters. Sampling was conducted over 14 days in July 2025 using umbrella traps, fishing rods, and underwater camera observations at three observation stations. The results of the study showed that there were six fish species, namely Rasbora lateristriata (Wader Pari), Barbodes binotatus (Wader Cakul), Oreochromis niloticus (Nila), Gambusia affinis (Cere), Nemacheilus fasciatus (Uceng), and Channa striata (Channa). The most abundant species was Wader Pari (25 individuals), while Channa was only one individual. Fish diversity in Sendang Seruni was classified as low with an H' value of 1. Clean, stable, and oxygen-rich water quality supports the existence of sensitive species such as B. binotatus, while polluted waters tend to be dominated by tolerant species. These results indicate the need for habitat management and conservation efforts to maintain the balance of the Sendang Seruni aquatic ecosystem.